Redes sociales y el rendimiento académico de los alumnos de Bachillerato, Unidad Educativa Diocesana San Luis de Otavalo, periodo actual - Molina Soto, Walter Fabian (2025)
In the study conducted with high school students of the San Luis de Otavalo Educational Unit, regarding the impact that social networks have on academic performance, to know how these platforms affect them either in a way that prevents them from developing their homework, concentrate, take time or when they are in class they are tired and their performance is not at one hundred percent, It was also evaluated how beneficial it is for students to use these platforms where they can find quick and clear information, where it can be a useful tool for their homework, or where they can deepen their knowledge in an extracurricular way, where they can also communicate either with their classmates or tutors immediately, for any questions or confirmation that occurs in their study. The objective was to analyze the impact of social networks in the educational environment, in high school students of the Diocesan Educational Unit San Luis de Otavalo, at present, which was fully met, worked directly on the entire population in this case of students and also in conjunction with teachers, In order to evaluate each of the benefits that the networks have, the problems that we found by the use of the same and also how these platforms could be integrated into the educational environment so that they are a working tool that supports the process of participatory and collaborative teaching and learning in an academic way